Museums and Galleries of Greece and Cyprus. - Iakovakis, Lucas; Kontou, Maria I. ([Athens] : Ministry of Culture, 1993)
Historical Museums, Museums of Natural History, Maritime Museums, Museums of Science and Technology, Art Museums, Theatrical Museum, Galleries of Art, Museums of Cyprus
Engels
boek
Keywords: Cyprus; Griekenland